Perlindungan Hukum Terhadap Kelompok Minoritas: Studi Kasus Diskriminasi Terhadap Mahasiswa Asal Papua Di Surabaya Pada 16 Agustus 2016 - Ghozali, Muhammad; Nora Liana; Cut Afra; Zulfadly Siregar; Nurfahni (Cendekia : Jurnal Hukum, Sosial dan Humaniora, 2024)
Indonesian law, including the Constitution and international treaties such as the ICCPR and ICERD, strictly prohibits racial discrimination and violence against minority communities. This legal protection ensures that the rights of minority groups are upheld and respected. Even though there is legal protection, cases of discrimination against Papuan students are often ignored by the government and ignore their human rights. This study will take a normative legal perspective in examining the validity of laws and regulations through comprehensive presentation and analysis. The purpose of this research is to investigate the social science paradigm by analyzing the effectiveness of law enforcement policies, the enforcement of those regulations, and the ability of law enforcement agencies and government entities to protect citizens from discrimination. This study highlights the root causes of discrimination against Papuans, which originate from racial bias in various aspects such as economics, politics, education and law enforcement. This emphasizes the importance of enforcing anti-discrimination laws with the highest professionalism among law enforcement officials to prevent the continuation of discriminatory practices in the legal system. In this study, it is recommended that the Indonesian Government increase its commitment to enforcing laws against discrimination and violence, especially in terms of protecting the rights of the Papuan ethnic community. This includes taking firm action if discrimination or violence occurs, in order to uphold justice and equality for all citizens.